High-density three-dimensional graphene cathode with a tailored pore structure for high volumetric capacity zinc-ion storage. (January 2022) - Xu, Xiangcheng; Zhao, Xijian; Yang, Zihong; Lin, Qiaowei; Jian, Bangquan; Li, Na; Zheng, Cheng; Lv, Wei
Abstract: Zinc-ion hybrid supercapacitors (ZHCs), based on the multivalent ion storage principle, are considered to be a promising candidate for large-scale energy storage devices. However, with the increasing demands for portable and miniaturized energy storage devices, how to obtain sufficient energy output in a limited volume is particularly critical, so that requires high volumetric energy density with no sacrifice of power density. Herein, we designed a compact three-dimensional porous graphene (3D-PG-1) cathode for ZHCs to balance the porous structure and high density by drying the graphene hydrogel with a short period of capillary evaporation. As for 3D-PG-1, the pore size range is 0.6–10 nm, where the micropore is for high capacity and the mesopore helps Zn 2+ rapid transport, and the high density of 1.38 g cm −3 guaranteed its high volumetric capacitance. Therefore, the ZHC based on this 3D-PG-1 cathode delivered an excellent volumetric performance of 299 F cm −3 at 0.1 A g −1, excellent long cycle stability (225 F cm −3 at 5 A g −1, 85% retention after 30000 cycles) and extremely high volumetric energy density up to 118 Wh L −1 at 116 W L −1, which retained 61 Wh L −1  at the power density as high as 23.2 kW L −1 . Graphical abstract: Image 1